Ruang Publik dan Paradigma Pendidikan Integralistik: Dari Interaksi Komunikatif Menuju Implementasi Kurikulum Berbasis Perjumpaan - Alexander, Michael (Faculty of Theology Duta Wacana Christian University, 2021)
AbstractThe public sphere is a meeting space. Various identities meet and interact. Each carries its pattern: instrumental-hierarchical, strategicmonological, or mutual-communicative. Equality in the last pattern is the basis for building relationships that are oriented towards realizing common goals which are formulated from the synthesis of ideas. This research shows that there is a gap between the idea of inter-particularities equality and the tendency of the respondents to prioritize group identities over efforts to create common welfare. This gap can be traced back to the design of the lectionary sermon which found a lack of discussion on the themes of the public space. Therefore, the author proposes analternative paradigmatic model that integrates all personal dimensions into the global-public dimension. A participatory approach that raises experiences in the context of community life is used as a starting point to mobilize the active participation of the people in testing the sermons relevance in the public space. AbstrakRuang publik merupakan ruang perjumpaan. Berbagai identitas bertemu dan berinteraksi. Masing-masing membawa polanya: instrumental-hierarkis, strategis-monologis, atau mutual-komunikatif. Kesetaraan dalam pola terakhir merupakandasar untuk menjalin relasi yang berorientasi pada upaya mewujudkan tujuan bersama yang dirumuskan dari sintesa gagasan-gagasan. Penelitian ini menunjukkan terdapatnya kesenjangan antara gagasan kesetaraan antarpartikularitas dengan kecenderungan umat responden yang mengutamakan identitas kelompok di atas upaya mewujudkan kemaslahatan bersama. Kesenjangan tersebut selanjutnya dirunut kembali pada rancangan khotbah leksionari dan dijumpai minimnya pembahasan mengenai tema-tema ruang publik. Oleh sebab itu, penulis mengusulkan sebuah model paradigmatik alternatif yang mengintegrasikan seluruh dimensi personal ke dalam dimensi publik global. Pendekatan partisipatori yang mengangkat pengalaman dalam konteks hidup bermasyarakat dipergunakan sebagai titik tolak guna memobilisir partisipasi aktif umat dalam mengujicobakan relevansi berita mimbar di ruang publik.